Analysis of student misconceptions using the five-tier diagnostic test on the concepts of vibration, waves, and light - Hasanah, Ita Izatul; Wulandari, Ana Yuniasti Retno; Qomaria, Nur; Yamin, Yamin; Sutarja, Maria Chandra (IAIN Palangka Raya, 2025)
The purpose of this study was to determine the percentage of students' misconceptions using the five-tier diagnostic test on the concept of vibration, waves, and light at UPT SMPN 21 Gresik. This study used a quantitative descriptive research method. The population in this study consisted of all students in grade VIII, which consisted of three classes. Sampling was carried out using saturated samples with a total of 80 students divided into three classes, namely class VIIIA, VIIIB, and VIIIC. The data collected used the fivetier diagnostic test instrument. The results of the study showed that: 1) the percentage of classical misconceptions from 80 students was 23,60%, 2) students who experienced high category misconceptions on the concepts of vibration, waves, and light were 14 students with a percentage of 17,50%, students who experienced moderate category misconceptions were 52 students with a percentage of 65,00%, and students who experienced low category misconceptions were 14 students with a percentage of 17,50%, 3) students' misconceptions on the concept of vibration were 28,82%, the concept of waves was 21,18%, and the concept of light was 24,47%.